(untitled) (Bangladesh Journal of Plant Taxonomy, 2020)
Preliminary taxonomic survey of aquatic plants of Feni district was conducted between July 2016 and June 2017. Traditional taxonomic techniques and random meander methods were applied to record and collect aquatic plant species. A total of 56 aquatic plant species under 29 families were recorded from Feni district. Ecological habitats of aquatic plant species showed variations. Among them, 30% species prefer to grow near the edge of water, 20% as rooted submerged, 18% as rooted emergent, 16% as free floating, 12% as rooted floating and 4% surface creeper in the aquatic habitat. The uses of aquatic plants were showed that 27% species were used as fodder, 14% as medicinal, 11% as vegetable, 11% as edible fruits, 5% as duck weeds, 2% as artifacts and 30% as others purposes in the study area. Abundance of aquatic plant species in the habitat was showed variations. Among them 9% was found very abundant, 30% found common and 61% found rare in the study area. Based on the field observations and discussion with local people we were able to identify a good number of threats to aquatic plants and also pointed out some conservation measures for them. It was seemed that the species Achyranthes aquatica (thuash), Oenanthe javanica (painnaadani), and Chumannianthus dichotomus (patipata) were found to be limited in distribution outside Feni. These rare species need to be given priority for in situ and ex situ conservation. Bangladesh J. Plant Taxon. 27(1): 103-111, 2020 (June)